Design of an isolated bidirectional resonant DC-DC converter with wide input voltage range for medium power applications / Asif Mustafa - Asif , Mustafa (2021)
Isolated Bidirectional DC-DC converters (IBDCs) are mainly used to provide reliable and good quality power in various electrical applications such as uninterrupted power supply (UPS), DC micro-grid with energy storage systems (ESSs), electric vehicles, vehicle-to-grid (V2G), grid-to-vehicle (G2V) and many more. Among several IBDCs, the single-phase resonant converter is mostly preferred owing to its minimized switching losses, high reliability, high power density, reduced electromagnetic interference, and ability to operate at high frequency. Nevertheless, it has the limitations of circulating power flow and limited soft-switching range for wide input voltage and load range variations. This research provides a novel topology for dual-phase LLC resonant converter with an improved variable frequency based zero circulating current phase shift modulation (VFPSM-ZCC). The topology is based on H6 inverter topology able to generate two square voltage waveforms and provide a dual-phase for two symmetrical resonant tanks and its high-frequency transformers, which are connected in series. The arrangement leads to a reduction of voltage stress across upper and lower switches to half of the input voltage that can be useful at high voltage input conditions. On the secondary side of the high-frequency transformer, an identical six-switch arrangement as an active rectifier is employed that becomes the critical component in energy storage systems (i.e., batteries, super-capacitors) for the purpose of bidirectional power flow. The converter is capable of achieving ZVS for primary as well as secondary switches for a wide variation of input voltage and output load. The proposed modulation scheme is a 3-variable control that enables the converter to operate with increased voltage gain range under all input voltage and loading conditions. Variable frequency control leads to the soft-switching operation of the switches connected to the primary side for all load ranges. The phase shift control is used as power transfer control along with maintaining a constant output voltage under changing input voltage. Moreover, the duty cycle calculation based on load conditions helps in eliminating the reverse power flow (RPF) due to circulating current, especially under light-load conditions, thereby increasing the conversion efficiency in comparison to the conventional dual active bridge converter. The inherent ability of frequency selection based on the loading conditions also minimizes the RMS resonant current that reduces the conduction losses while operation, especially under light-load conditions. To verify the performance of the proposed converter and employed modulation scheme, a 1.5kW prototype with 210V-400V input and 80V output is built, and the experimental results have been presented. The measured efficiency of the built PCB prototype of the converter at full load is 96.7% and 94.2% under maximum and minimum input voltage conditions, respectively.